2014
DOI: 10.1111/apt.12963
|View full text |Cite
|
Sign up to set email alerts
|

Performance and limitations of steatosis biomarkers in patients with nonalcoholic fatty liver disease

Abstract: Summary Background Several steatosis biomarkers are available with limited independent validation. Aim To determine diagnostic value and limitations of several steatosis biomarkers using liver biopsy as reference standard in a large cohort of patients with suspected NAFLD. Methods Three hundred and twenty‐four consecutive liver biopsies were included. Histological steatosis was categorised as none (<5%), mild (5–33%), moderate (33–66%) and severe (>66%). Five steatosis biomarkers were measured: fatty liver ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
344
3
23

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(383 citation statements)
references
References 57 publications
(80 reference statements)
13
344
3
23
Order By: Relevance
“…All these biomarkers could diagnose steatosis and were correlated with insulin resistance. 17 However, they are confounded by fibrosis and inflammation and did not accurately quantify steatosis. The prognostic value of CAP needs to be evaluated and compared with FLI.…”
Section: Discussionmentioning
confidence: 99%
“…All these biomarkers could diagnose steatosis and were correlated with insulin resistance. 17 However, they are confounded by fibrosis and inflammation and did not accurately quantify steatosis. The prognostic value of CAP needs to be evaluated and compared with FLI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that stage 2 fibrosis has highest misclassification rate on noninvasive techniques. 7,26,27 In spite of this till today LB is used in suspected cases of autoimmune hepatitis, primary sclerosing cholangitis, primary biliary cholangitis, NASH, cryptogenic cirrhosis, infections such as CMV or EBV, and liver tumors not well defined by imaging techniques. 6 With this reference, a study was planned to determine utility of LB in day-to-day hepatology practice.…”
Section: Discussionmentioning
confidence: 99%
“…Têm a vantagem de prever também o aparecimento de complicações metabólicas, hepáticas e cardiovasculares. 26 No entanto, têm mais aplicabilidade em estudos populacionais/epidemiológicos, pois, considerando o indivíduo, a esteatose deve ser identificada preferencialmente por ecografia.…”
Section: Diagnósticounclassified